Correlation Between Prolonged Mask Use and the Severity of Acne Vulgaris Among Medical Students at Nusa Cendana University During the COVID-19 Pandemic - Tungga, Charlie Eunike Novanty; Lidia, Kartini; Dedy, Maria Agnes Etty; Oematan, Herjuni (Cendana Medical Journal, 2025)
Abstract Background: At the end of 2019, the Corona-virus Disease (COVID-19) spread through droplets and direct contact, causing a high rate of transmission so and it became a worldwide pandemic. To prevent the spread of COVID-19, health protocols are applied to the entire community, namely: wearing masks, social distancing, and washing hands. The use of masks for long durations can cause acne vulgaris or commonly known as maskne. Medical Faculty students have good knowledge so that they can carry out good Health protocols. Objective: to determine the relationship between the duration of using masks on the severity of acne vulgaris in students of the Faculty of Medicine, University of Nusa Cendana, during the COVID-19 pandemic. Methods: The research method is observational analytic using a cross-sectional design conducted on preclinical students of the Faculty of Medicine, University of Nusa Cendana through a media zoom meeting, Google form, and taking direct facial photos by researchers, then the severity of acne vulgaris is assessed by a doctor. genital skin specialist. The sampling technique is purposive sampling, with the number of respondents being 76, and using the Chi Square test. Results and discussion: From this study obtained 76 respondents. Respondents with a duration of wearing a mask <3 hours are 39 (51.3%), and respondents with a duration of wearing a mask >3 hours are 37 (48.7%). The results showed that the severity level of the acne vulgaris on students of the Faculty of Medicine Undana classified as mild are 54 people (71.1%), and moderate classification as many as 22 people (28.9%). The results of the bivariate test in this study obtained the results of p = 0.000 (p <0.05) Conclusion: There is a relationship between the duration of wearing masks and the severity of acne vulgaris in medical students at the Nusa Cendana University during the COVID-19 pandemic.